The causal factors of varietal ununiformity in wheat (Triticum aestivum (L.) Thell) and the role of chromosomal instability - Fernandes, Maria Irene B. de M.; Bodaneze-Zanettini, Maria Helena; Zanatta, Ana Christina A. (Pesquisa Agropecuaria Brasileira, 1991)
Mechanical mixtures, natural crosses, segregation from original cross and recurrent chromosomal instability are the main factors that cause varietal ununiformity. Joint experiments carried out at CNPT/EMBRAPA in Passo Fundo, RS, Brazil, and at the UFRGS laboratories showed that drastic climatic fluctuations, fungal and virus diseases, agrochemicals and soil acidity may increase the incidence of chromosomal abnormalities in wheat (Triticum aestivum (L.) Thell), but the main determining factor is the genotype. Norin 10 germoplasm presents, for exemple, higher levels of cytological instability than Brazilian varieties. Meiotic stable plants from abnormal cultivars originated more fertile progenies than unstable ones, showing that, in those cases, it is very important to select uniform progenies for the Foundation Seed Stocks. However, the selection of cytological stable progenies in cultivars with high instability showed that it is recurrent and that it can only be minimized. Specific recommendations to breeders and seed producers are made on this subject.